SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN PINJAMAN KREDIT MENGGUNAKAN METODE TOPSIS PADA CUM CARITAS HKBP PEMATANGSIANTAR - Sahat Sonang; Arifin Tua Purba; Victor Marudut Mulia Siregar (Politeknik Bisnis Indonesia, 2020)
This research was conducted to solve the problem of decision making to determine the feasibility of giving loans to CUM Caritas HKBP Pematangsiantar. The applicant's assessment includes an administrative assessment and the survey is still being conducted without using a computer-based decision support system. To simplify the decision making to determine the feasibility of giving the loan, a decision support system was designed using the Topsis method (Technique for Order Preference by Similarity to Ideal Solution). The criteria used consist of: Income, Dependent, Loan Size, Guarantee Value and Number of Installments. The results of the calculation of the case of this study that are eligible for a loan in order are NA2 with a value of 0.6390, NA1 with a value of 0.5737, the third is NA3 with a value of 0.5053, and the last is NA4 with a value of 0.3102. The results of this study can be concluded that the Topsis method can answer or resolve problems faced by CUM Caritas HKBP Pematangsiantar in determining creditworthiness.